Crevice corrosion of duplex stainless steels in the presence of natural marine biofilms - Machuca, Laura; Bailey, Stuart; Gubner, Rolf; Watkin, Elizabeth; Ginige, Maneesha; Kaksonen, Anna (Nace International, 2012)
The evaluation of crevice corrosion of high alloy stainless steels used in offshore applications is of major importance as it is one of the most deleterious forms of localized corrosion which may result in sudden marine corrosion failure. The resistance of UNS S31803 duplex stainless steel (DSS) to crevice corrosion in natural seawater was evaluated by immersion and electrochemical tests. Artificially creviced specimens were tested before, during and after immersion in natural seawater under stagnant conditions for up to eight weeks allowing indigenous marine microorganisms to adhere to the alloy surface and form a biofilm. The changes in biofilm community structure and the influence of biofilm on the crevice corrosion of DSS specimens in seawater were investigated at two different exposure times (4 and 8 weeks) using a combination of potentiodynamic and potentiostatic measurements, surface inspection and bacterial community profile analysis by 16S rRNA gene PCR-DGGE and DNA sequencing. Results indicate that our selection approach to evaluate crevice corrosion yields highly reproducible results. Crevice corrosion was observed only in electrochemically polarized specimens that had been exposed to natural seawater containing bacteria. The possible mechanisms involved in the biofilm enhanced crevice corrosion are discussed.